Kajian Tentang Kode Etik Guru Terkait Penghormatan Terhadap Hak Asasi Manusia - Della Pebriani Simamora; Desi Marlina Sidabutar; Edoward Fran Silalahi; Juni Kristiani Meliala; Ramona Febiola Simorangkir; Sinta Uli Nainggolan; Tiur Intan Febiana Hutauruk; Jamaludin Jamaludin; Sri Yunita (Universitas 45 Surabaya, 2025)
This research is entitled “Study of Teacher Codes of Ethics Regarding Respect for Human Rights”. This research analyzes how teachers as educators and mentors have a crucial role in shaping the character and morals of students. Therefore, understanding and implementing a code of ethics that upholds human rights is very important. Using qualitative methods, this research analyzes various regulations, teachers’ professional codes of ethics, and other related literature. The research results show that the code of ethics for teachers in Indonesia explicitly includes teachers’ obligations to respect students’ human rights. This includes the right to receive an adequate education, the right to be free from discrimination and violence, and the right to participate in the learning process. However, the implementation of the code of ethics still faces various challenges, such as teachers’ lack of understanding of human rights, lack of supervision and enforcement of the code of ethics, and the existence of a school culture that does not fully support respect for human rights. This research concludes that the implementation of a teacher’s code of ethics in respecting students’ human rights is very important in ensuring that students feel respected and valued in the teaching and learning process. Therefore, teachers must understand and implement the applicable code of ethics in respecting students’ human rights.